(untitled) (Biocenosis, 2023)
The province of Guanacaste has been subject to an increase in real estate development and its road network. This increase in national and cantonal streets has fragmented the habitat and changed the natural dynamics of ecosystems and their wild populations. Traffic through National Route 21 in the canton of Carrillo has generated a negative impact on birds, wild mammals and especially on herpetofauna.